Variation in Morphometric Characters in Four Sand Crab (Albunea symmysta) Populations Collected from Sumatra and Java Island, Indonesia - Febi Ayu Pramithasari; Nurlisa Alias Butet; Yusli Wardiatno (Tropical Life Sciences Research, 2017)
Variation in morphometric characters in four sand crab (Albunea symmysta) populations from four intertidal areas in Sumatra (Aceh and Bengkulu) and Java (Cilacap and Yogyakarta) were studied. Crabs collected from the four sites were measured to obtain 10 morphometric characters, i.e., carapace length (CL), carapace width (CW), ocular peduncle length and width (LOP and WOP), telson length and width (LT and WT), merus length (ML), carpus length (CaL), propodus length (PL), and dactylus length (DL). Allometric relationships were established among three morphometric characters (CW, PL, and DL) for each site, in which CL was fixed on the abscissa as a reference variable. The analysis of covariance showed that population from Yogyakarta had a greater carapace width and the Aceh population had a longer dactylus length. In terms of propodus length, the Aceh population had a longer dactylus length than the Bengkulu population. Two group populations were detected by cluster analysis with 10 morphometric characters, i.e., the Sumatra population and the Java population.